Staphylococcus biofilm dynamics and antibiotic resistance: insights into biofilm stages, zeta potential dynamics, and antibiotic susceptibility - T. Lavoie; K. E. Daffinee; M. L. Vicent; K. L. LaPlante (Microbiology Spectrum)
ABSTRACT Staphylococcus spp. infections often involve biofilms, but standard antibiotic minimum inhibitory concentration (MIC) testing used to determine treatment evaluates planktonic bacterial growth only and does not account for biofilm presence, strength, or growth stage. To aid in determining a cost-effective method to solve this issue, we built upon in vitro methods initially published by Stepanovic et al. used to determine weak and strong biofilm formations. First, we determined 115 unique S. aureus isolate biofilms at 2, 4, 6, 8, 16, and 24 h to classify the hourly stages of biofilm development based on statistically significant final growth results (P < 0.001): stages one (0–6 h), two (6–16 h), three (16–24 h), and four (>24 h). Next, to further evaluate in vitro biofilm strength, electrostatic differences were measured through zeta (ζ)-potential for strong and weak biofilm producers at early and late stage-formed biofilms. The early stages of weak biofilm formers had a greater negative electrostatic charge when compared to strong biofilm formers. Meanwhile, strong biofilm formers began early stages with less negative charges before increasing the negative electrostatic charge by stage-four biofilm. At all time points, weak biofilm-forming isolate mean ζ-potentials were significantly more negative than strong biofilm formers (P = ≤0.04). Finally, to elucidate minimum eradication concentrations for biofilms, we treated stage-four biofilms with progressively higher concentrations of either daptomycin, vancomycin, or levofloxacin. Daptomycin was the only antibiotic to achieve ≥75% reduction in biofilm viability, seen at 32–256 μg/mL (64–512× MIC), and significantly reduced residual biofilm across all strong and weak biofilms. Biofilm findings showed an unexpected initial biofilm decrease in response to lower concentrations of antibiotics, followed by an increase in biofilm biomass at higher antibiotic concentrations. While higher antibiotic concentrations can be used to overcome bacterial resistance and eliminate infections, our results suggest that antimicrobial resistance is observed, regardless of bacterial biofilm strength, and that there may be an optimal treatment concentration window for achieving maximum kill. Our data add to the increasing evidence of biofilms’ role in recurrent infections and the importance of antibiotic concentration.IMPORTANCEThis work is significant, as it addresses a critical gap in standard antibiotic testing by focusing on the unique characteristics of biofilm-forming Staphylococcus aureus infections, which are major contributors to recurrent and chronic infections. Unlike traditional MIC testing that evaluates planktonic bacteria, this study emphasizes the importance of biofilm presence, growth stages, and electrostatic properties in determining treatment strategies. By classifying biofilm development into distinct stages in an easily reproducible assay and measuring the biofilm zeta-potential for key differences and overall biofilm response to multiple standard antibiotic concentrations, this research provides valuable insights for the future of biofilm in vitro work. Furthermore, it highlights the efficacy of daptomycin in eradicating biofilm while identifying possibilities of optimal antibiotic concentration windows, a critical consideration for mitigating resistance and achieving effective infection control. These findings underscore the necessity of tailoring treatment to biofilm-specific dynamics, offering a path toward more effective therapeutic approaches for biofilm-associated infections.